Amul: Evolution of an International Brand - Asthana, A. K. (Indian Journal of Marketing, 2012)
Kaira District Cooperative Milk Producers’ Union Limited, also known as ’Amul dairy’ sold milk powder and butter in the regional market of Gujarat and Bombay way back in 1955 under the brand name ’Amul’. The brand revolved around Amul butter for brand awareness and brand equity. It soon transformed from a single product brand to a family brand. GCMMF in 1973 acquired the right to manage Amul brand for trade purposes, selling various milk and milk based food products in the pan India market under the Amul brand. Due to high brand equity, Amul brand became the No.1 food brand of India. Amul brand crossed the Indian shore and also emerged as the No.1 brand in the Asia Pacific market. This way, Amul travelled a long journey from its status of being a regional brand to an international brand. This paper strives to trace the attributes and process of transformation of Amul from being a regional brand to an international brand.